A study of the giant swings prior to the different types of flight elements on horizontal bar - Angelov, V.; Kyuchukov, I.; Andreev, P. (Research in Kinesiology, 2017)
The aim of this study is to model the technique of the giant swings prior to the riskiest and most attractive exercises - the flight elements. The subjects under examination are the following kinematic parameters: joint angles in key operating positions, the linear velocity of the centre of gravity, the distance between the centre of gravity and the grip, as well as the angle of leaving the apparatus. Contingent of thestudy are the finalists in the horizontal bar Championship at the World Cup Gymnastics in town of Varna in 2015. All of the giant swings, that are subject of this study, are characterised with a sequence of folding and unfolding movements mainly in the shoulder and pelvis joints in the appointed four zones. The difference in the amplitude in these movements determines the size of the linear speed of COG in the fifth working positions. Scientific methods such as video making, videocyclography, kinematic analysis, pedagogical surveillance, expert evaluation, analytic and synthetic methods and mathematic methods are used for the sake of the examination. The main structural group of horizontal bar exercises are determined. The composite structure of the competitive routines is analyzed. The collected data from the kinematic examination is systematized in charts. Graphics are prepared for some of the parameters. An analysis is made based on the received results.